Toward a Theory of Entrepreneurial Careers - Dyer, W. Gibb (Entrepreneurship Theory and Practice, 1995)
Parallel streams of theory and research regarding entrepreneurship and careers has led to a dearth of comprehensive theories regarding the careers of entrepreneurs. This article describes four core dimensions of theory that are essential in developing a comprehensive theory of entrepreneurial careers: (1) a theory of career choice; (2) a theory of career socialization; (3) a theory of career orientation; and (4) a theory of career progression from entry to exit. A general model is presented that articulates various aspects of theory building along each of these four dimensions. Implications for both theory and practice regarding entrepreneurial careers is also discussed.